Adjuvant 5‐Fluorouracil/leucovorin, capecitabine, and oxaliplatin‐related regimens for stage II/III colon cancer patients 66 years or older - Emily Jones; Zhigang Duan; Thinh T. Nguyen; Sharon H. Giordano; Hui Zhao (Cancer Medicine)
Abstract Adjuvant chemotherapy of leucovorin‐modulated 5‐fluorouracil (5‐FU/LV), capecitabine, and adding oxaliplatin to 5‐FU/LV or capecitabine (FLOX/OX) have been standard regimens for high‐risk stage II or III colon cancer (CC). We aimed to evaluate their patterns of use, association with survival, and rate of emergency room visit (ER) or hospitalization during the treatment period. High‐risk stage II or III patients aged >65 years diagnosed between 2007 and 2015, underwent colectomy, and received any of these three regimens were selected from SEER and Texas Cancer Registry (TC) linked with Medicare data. Chi‐square test, Kaplan–Meier survival curves, Cox regression, and logistic regression were used in data analysis. A total of 5621 (1080 stage II and 4541 stage III) patients with median age of 72 years were included in this study. For stage II, 24.4% used 5‐FU/LV, 31.2% used capecitabine, and 44.4% used FLOX/OX; the respective numbers for stage III were 13.8%, 17.9%, and 68.3%. Patients aged <70 years, not in the West region, not in Medicare state‐buy‐in program, and with no comorbidity were more likely to use FLOX/OX. FLOX/OX was associated with improved overall survival (OS) in stage II and III patients and improved cancer‐specific survival in stage III patients compared with 5‐FU/LV. The survival benefit of FLOX/OX was sustained in stage III patients aged ≥70 years. Capecitabine had the lowest ER/hospitalization rate with 19.2% in stage II and 28.9% in III. The use of FLOX/OX was associated with improved survival compared with 5‐FU/LV among CC patients. Capecitabine was associated with the lowest ER/hospitalization rate.